Salivary levels of SIgA and perceived stress among dental students - Sangiorgio, João Paulo Menck; Seixas, Gabriela Fleury; de Paula Ramos, Solange; Dezan-Garbelini, Cássia Cilene (Journal of Health & Biological Sciences, 2017)
Background: Academic stress may impair mucosal immunity and expose dental students to an increased risk of infections. Objective: to assess stress scores in dental students and their relationship with variation in SIgA levels. Methods: All students (n = 289) were invited to take part of the study, and 207 (71.63%) effectively participated, being 152 (73.4%) females. At the day of data collection, the students answered The Dental Environmental Stress Questionnaire (DES) and unstimulated saliva samples were collected for determination of salivary flow rate and SIgA concentration and secretion rate. Results: Mean DES scores were higher in females (78.97 ± 16.42), but no correlations between the sum of DES scores and salivary parameters were observed (P=0.08). A moderate inverse relationship was observed between SIgA secretion rates and the subscales Academic Performance (P=0.01), Interpersonal relationships (P=0.02) and Difficulties and Insecurities about Professional Future (P=0.05). A weak correlation was found between SIgA concentration and the items Amount of assigned classwork (P=0.02), Lack of confidence in self to be a successful dentist (P=0.01), Lack of time for relaxation (P=0.01), Financial responsibilities (P=0.02) and Personal physical health (P=0.005). Weak correlations between SIgA secretion rates and DES items were also found for Lack of cooperation by patient in their home care (P=0.003), Patients being late or not showing up for their appointments (P=0.02), Lack of self confidence to be a successful dentist (P=0.008), Personal physical health (P=0.019), and others. Conclusion: Different sources of stress were observed among first to fifth year students and some of these stressors may negatively impact on salivary SIgA secretion.